Bibliometric analysis and description of research trends in the treatment of psoriasis with biologic agents in the past two decades (2004-2023) - Yingdong Wang; Junchen Li; Chenqi Guo; Guojing Yang; Haiyue Lin; Yu Zhang (Taylor & Francis Group, 2024)
Background Biologics are essential in treating psoriasis. In recent years, the pathogenesis exploration and development of new target drugs have provided a more complete evidence-based foundation for the biological treatment of psoriasis. This study aims to use bibliometrics to analyze the research status and development trends of biologics in psoriasis.Methods The bibliometric analysis of publications related to biologics in psoriasis from 2004 to 2023 was conducted using the Web of Science Core Collection (WoSCC) database as the search data source. To perform the bibliometric analysis and create visual knowledge graphs, CiteSpace, the Bibliometrix R package, and VOSviewers were utilized.Results The study included a total of 3800 articles. The United States had the highest number of publications. The leading authors and institutions were Steven R. Feldman and the University of Manchester, respectively, in the global partnership. The cluster plot divided all keywords into 11 categories. Currently, Secukinumab and Guselkumab are representative biological agents being studied due to their considerable efficacy and long-term safety.Conclusions Targeted therapy has emerged as a significant trend in the current treatment of psoriasis. Early and active use of biologics can effectively control disease progression, prevent or delay the occurrence of comorbidities, and may even alter the natural course of psoriasis. However, further investigation is required to fully understand the specific mechanisms of psoriasis and the use of biological agents.